2022
DOI: 10.30892/gss.1704-087
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Small-Scale Sporting Events in South Africa

Abstract: This article evaluates the impact that COVID-19 has had on small-scale sporting events within the context of South Africa. To this end, it considers the impacts that the pandemic has had on these types of events, and reflects on the strategic direction in the management and organisation of these events going forward. To achieve this, a content analysis of existing frameworks and documentary analysis of government policies and strategies, coupled with interviews with stakeholders involved in the organisation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Other sport performers, such as coaches and referees were also experiencing meaningful changes to their sport engagement and career trajectories (Ilies et al, 2021, Mchunu et al, 2022, feeling less publicly essential than they were used to (Taku and Arai, 2020). It was suggested that elite referees faced issues, such as quarantine, time away from families and loved ones, a lack of ongoing contact with colleagues and fiscal concerns (Webb, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other sport performers, such as coaches and referees were also experiencing meaningful changes to their sport engagement and career trajectories (Ilies et al, 2021, Mchunu et al, 2022, feeling less publicly essential than they were used to (Taku and Arai, 2020). It was suggested that elite referees faced issues, such as quarantine, time away from families and loved ones, a lack of ongoing contact with colleagues and fiscal concerns (Webb, 2020).…”
Section: Introductionmentioning
confidence: 99%